2021
DOI: 10.1155/2021/8846779
|View full text |Cite
|
Sign up to set email alerts
|

Innovative Landslide Susceptibility Mapping Portrayed by CA‐AQD and K‐Means Clustering Algorithms

Abstract: This study aims at proposing and designing an improved clustering algorithm for assessing landslide susceptibility using an integration of a Chameleon algorithm and an adaptive quadratic distance (CA-AQD algorithm). It targets improving the prediction capacity of clustering algorithms in landslide susceptibility modelling by overcoming the limitations found in present clustering models, including strong dependence on the initial partition, noise, and outliers as well as difficulties in quantifying the triggeri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 56 publications
0
4
0
Order By: Relevance
“…Based on the existing LSM literature in the study area, landslide susceptibility is usually classified into 5 levels: very high susceptibility level (VHSL), high susceptibility level (HSL), moderate susceptibility level (MSL), low susceptibility level (LSL), and very low susceptibility level (VLSL) [43,44,46,47,60,89,90]. However, the DIANA and ROCK methods categorized the mapping units (points/objects as used in the methods) to their respective subclasses, but did not identify the susceptibility levels in the subsets.…”
Section: Methods For Landslide Susceptibility Classificationmentioning
confidence: 99%
“…Based on the existing LSM literature in the study area, landslide susceptibility is usually classified into 5 levels: very high susceptibility level (VHSL), high susceptibility level (HSL), moderate susceptibility level (MSL), low susceptibility level (LSL), and very low susceptibility level (VLSL) [43,44,46,47,60,89,90]. However, the DIANA and ROCK methods categorized the mapping units (points/objects as used in the methods) to their respective subclasses, but did not identify the susceptibility levels in the subsets.…”
Section: Methods For Landslide Susceptibility Classificationmentioning
confidence: 99%
“…Because of these limitations, SL methods may not be applicable where there are a limited number of labeled samples as they are not always easy to obtain and may be expensive to acquire in abundance through image interpretation and site surveying, especially in a large study area. USL-based approaches are applied and have contributed to improving the implementation and the accuracy of LSM in such situations (Lei et al, 2018;Hu et al, 2021;Yimin et al, 2021;Mao et al, 2022;Su et al, 2022;Liu et al, 2023). USL-based methods such as clustering can be used to map the susceptibility areas, as they can identify the underlying structures in unlabeled datasets, hence, do not require data with predefined labels, and do not involve a training process during their implementation.…”
Section: Introductionmentioning
confidence: 99%
“…Over decades, these methods have been widely used in other fields such as marketing research, pattern recognition, and image processing, but very rarely explored in LSM studies (Huang et al, 2020;Su et al, 2022). In recent years, making use of the advantages of these methods, some landslide researchers have also shown interest and conducted LSM studies using these methods (Wan et al, 2015;Wang et al, 2017;Hu et al, 2019;Mao et al, 2021a;Mao et al, 2021b;Hu et al, 2021;Pokharel et al, 2021;Yimin et al, 2021;Mao et al, 2022). From the analysis of these studies and other traditional clustering algorithms, some limitations were observed: the inability to detect subclasses with arbitrary shapes, sensitivity to noise, inability to perform well in large study areas with large datasets, and principally a standard method to process the uncertain data (rainfall) has not being obtained yet.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation